2019
DOI: 10.1001/jamapsychiatry.2019.1119
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Anxiety and Stress-Related Disorders

Abstract: IMPORTANCE Anxiety and stress-related disorders are among the most common mental disorders. Although family and twin studies indicate that both genetic and environmental factors play an important role underlying their etiology, the genetic underpinnings of anxiety and stress-related disorders are poorly understood. OBJECTIVES To estimate the single-nucleotide polymorphism-based heritability of anxiety and stress-related disorders; to identify novel genetic risk variants, genes, or biological pathways; to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 67 publications
3
124
1
3
Order By: Relevance
“…We note that two other anxiety disorder GWAS have been published since these analyses were performed. The first, conducted in 12,655 individuals with registry‐derived ICD‐10 anxiety and/or stress‐related disorders and 19,225 unscreened controls from the Danish Lundbeck Foundation Initiative for Integrative Psychiatric Research (iPSYCH) cohort, reported one genome‐wide significant association with variants in the PDE4B gene (Meier et al, ). The second, conducted in 25,453 cases with self‐reported any lifetime anxiety disorder and 58,113 controls from the UK Biobank cohort, identified five novel genome‐wide significant loci including variants in the gene for NTRK2 , a receptor for brain‐derived neurotropic factor (Purves et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We note that two other anxiety disorder GWAS have been published since these analyses were performed. The first, conducted in 12,655 individuals with registry‐derived ICD‐10 anxiety and/or stress‐related disorders and 19,225 unscreened controls from the Danish Lundbeck Foundation Initiative for Integrative Psychiatric Research (iPSYCH) cohort, reported one genome‐wide significant association with variants in the PDE4B gene (Meier et al, ). The second, conducted in 25,453 cases with self‐reported any lifetime anxiety disorder and 58,113 controls from the UK Biobank cohort, identified five novel genome‐wide significant loci including variants in the gene for NTRK2 , a receptor for brain‐derived neurotropic factor (Purves et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress evokes multiple behavioral and physiological responses 1 , 2 , including neuroendocrine and immune deficits 3 7 , that may trigger common affective illnesses, such as anxiety, depression and post-traumatic stress disorder (PTSD) 8 – 11 . Widespread, debilitating and often treatment-resistant, these neuropsychiatric disorders represent an urgent unmet biomedical problem 12 14 , complicated by their multiple overlapping genetic and environmental determinants, and poor understanding of their mechanisms and risk factors 15 , 16 . Animal models, especially employing rodents, are widely used to study stress biology and pathogenesis 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using this approach are beginning to show that common genetic variants (single‐nucleotide polymorphism; SNP) account for individual differences in depression and anxiety. Findings indicate that SNP‐based heritability of anxiety and depression varies between 0.10 and 0.30 (Howard et al, 2019; Meier et al, 2019; Otowa et al, 2016; Purves et al, 2019; Wray et al, 2018). SNP heritability is one way to show the cumulative contribution of a subset of SNPs to a trait's total heritability (Bulik‐Sullivan, Loh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%